Purification of kidney epithelial cell growth inhibitors. - Holley, R W (1980)
Two high molecular weight growth inhibitors have been isolated from the culture medium of BSC-1 cells, epithelial cells of African green monkey kidney. The purified kidney epithelial cell growth inhibitors, at ng/ml concentrations, reversibly arrest the growth of BSC-1 cells in the G1 phase of the cell cycle. Their action is selective; they are most active on BSC-1 cells, are less active as inhibitors of the growth of rat lung and human breast epithelial cells, and do not inhibit the growth of 3T3 mouse embryo fibroblasts ad human skin fibroblasts in culture. Their growth inhibitory action on BSC-1 cell cultures is counteracted by epidermal growth factor or calf serum.